The Role of Omnichannel and Experiential Marketing to Build Brand Association in ZAP Clinic - Alfina Alfina; Marisya Mahdia Khoirina; Muwahiddatul Ulya (Binus Business Review, 2021)
The development of online commerce, popularly known as online stores, has rapidly changed people's lifestyles. Lately, online shopping trends do not mean that offline stores are no longer prioritized, especially in beauty clinics that sell their services and products. ZAP Clinic Indonesia is a beauty clinic focusing on offline and online sales to increase the company's brand equity. The research aimed to determine and analyze the effect of omnichannel and experiential marketing on brand association using the Customer-based Brand Equity (CBBE) method. The research applied a quantitative approach with a sample size of 101 respondents. The respondents were the consumers who had visited and tried the services and products of ZAP Clinic in Surabaya. The sampling technique was accidental sampling with a questionnaire as the instrument. Then, data were analyzed using the multiple regression analysis method to determine whether omnichannel and experiential marketing affected the brand association at ZAP Clinic. The results show that omnichannel and experiential marketing have a positive effect on brand association. Experiential marketing has a dominant value to create a stronger positive association. Moreover, omnichannel will boost the creation of brand association about ZAP Clinic through the marketing campaigns and delivering new experiences related to technology usage in skincare treatment.